A new flortaucipir PET biomarker based on graph theory for early detection of CTE in former American football players. (20th December 2022) - Protas, Hillary D.; Su, Yi; Luo, Ji; Chen, Kewei; Alosco, Michael L; Adler, Charles; Balcer, Laura; Bernick, Charles B.; Au, Rhoda; Banks, Sarah J; Barr, William; Coleman, Michael J; et al.
Abstract: Background: Chronic traumatic encephalopathy (CTE) is a neurodegenerative disease that is characterized by perivascular foci of phosphorylated tau (p‐tau) notably in the depths of sulci, with varying patterns in the cerebral cortex. Prior studies show elevated flortaucipir (FTP) PET binding in former American professional football players(PRO). However, the association of p‐tau with clinical measures remains unclear using regional FTP SUVR as early signs of CTE related tau pathology. Graph theory (GT) takes advantages of the spatial variability in p‐tau load and allows the integration of regional measures to define GT based measures. Here we examine the GT based measures in two CTE cohorts to evaluate their utility in assessing p‐tau related pathology in CTE. Method: The graph procedure was optimized in FTP PET images in a group of 26 PRO with reported cognitive and/or behavorial symptoms and 30 asymptomatic controls without a history of traumatic brain injury (the DETECT Study) and identified the GT measure, entorhinal tau strength, as the target metric with the best group separation between PRO and controls. The optimized graph procedures were then applied to the DIAGNOSE CTE Research Project dataset (99 former PRO, 51 former college football players [COL], and 52 controls without exposure to repetitive head impacts [CTL]) and we examined entorhinal tau strength's ability to differentiate the exposure groups and relationship to consensus based diagnoses of Traumatic Encephalopathy Syndrome (TES), the clinical syndrome associated with CTE. Result: Entorhinal tau strength was significantly different among the three exposure groups (p=0.0001) similar to regional SUVR measures (Figure 1). Regional SUVR did not differentiate players (PRO+COL) with and without TES, while entorhinal tau strength approached although did not reach significance (Figure 2). Entorhinal tau strength is the only FTP measure that showed significant differences (p=0.006) between those players with cognitive impairment and players without (Figure 3). Conclusion: While there is still considerable overlap in between‐group measurements, GT based entorhinal tau strength, is potentially more sensitive in detecting tau changes in players with and without TES. Additional studies are necessary to clarify the value of this new measure in detecting underlying CTE pathology.